ANALISIS CEMARAN MIKROBA PADA DAGING AYAM BROILER DI KOTA MAKASSAR - Sukmawati Sukmawati; Ratna Ratna; Ahmad Fahrizal (Scripta Biologica, 2018)
Broiler chicken is one of the source of animal protein, which is favored by Indonesian society, because it has economic value and its availability is easy to be obtained both in traditional market and in modern market. This aim of this study is to determine the amount of microbial contamination in broiler chicken meat in the area of Makassar city. The method used in this research was descriptive method, that was test analysis of microbial contamination on broiler chicken sample which area in Makassar city. Of the five samples the largest value of colonies is 242 sample as much as 2412 cfu/g, while the smallest value of colonies is 247 sample of 435 cfu/g. According to the results of this study can be concluded that broiler chicken meat in the area of Makassar city is recommended for consumption.